Physicochemical and microbiological analyzes of water from wells used in food production in a tourist complex in the State of Ceará (Research, Society and Development, 2021)
Water is an essential substance for all living beings, as well as essential to industry, commerce and services, especially food. However, it is known that Brazil, despite being a privileged country in relation to water reserves, has an unequal distribution of water reserves, as observed when comparing the North and Northeast regions. At the same time, the development of wells has become an important measure in an attempt to overcome the problems of sequestration in certain regions. This study aimed to analyze the water quality of two wells used in food production of a tourist complex outside the state of Ceará, through physical-chemical and microbiological parameters, in the period from 2019 to 2021. 37 analyzes were carried out, where the physicochemical parameters verified were: pH, Chlorides, Residual Chlorine, Total Hardness, Total Solids, Iron, Nitrate, Nitrite, Sodium and Turbidity. Microbiologically analyzed: total coliforms and Escherichia coli. The collection, conditioning and conservation procedures followed the methodology set forth in the Standard Methods for the Examination of Water and Wastewater. The results obtained indicated that the physicochemical parameters pH, Nitrate, Nitrite and Turbidity were satisfactory. The parameters of Chlorides, Total Solids, Iron, Sodium showed some type of non-conformity throughout the analysis in relation to the values ​​recommended by the Brazilian legislation and the WHO. The unsatisfactory microbiological parameters in relation to Coliforms totalized 17.95% of the analysis, in relation to E. coli there was only one failure, however, it can be explained by the low concentration of residual chlorine, not the same analog.